Respuesta :

Answer:

(2, - 4 )

Step-by-step explanation:

Given the 2 equations

x + 2y = - 6 → (1)

3x + y = 2 → (2)

Multiplying (2) by - 2 and adding to (1) will eliminate the term in y

- 6x - 2y = - 4 → (3)

Add (1) and (3) term by term to eliminate y

- 5x = - 10 ( divide both sides by - 5 )

x = 2

Substitute x = 2 into either of the 2 equations and solve for y

Substituting into (1)

2 + 2y = - 6 ( subtract 2 from both sides )

2y = - 8 ( divide both sides by 2 )

y = - 4

Solution is (2, - 4 )

ACCESS MORE